Pemberdayaan Peningkatan Kompetensi Pembelajaran Digital Bagi Calon Guru Sekolah Kejuruan melalui MOOC Rumah Vokasi - Riyadi Muslim; Herman Saputro; Danar Susilo Wijayanto; Ranto, Ranto; Ngatou Rohman (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2025)
Teachers have an important role to play in improving the competence of students in VET schools. Technological literacy in classroom management is often a teaching challenge. Today, many students are familiar with the use of modern technology, including access to knowledge. This is a great opportunity for teachers to facilitate students' access to information to learn complex things. Therefore, it is necessary to increase teachers' competence in interactive learning technology. The purpose of this service is to increase the technological competence of pre-service teachers and teachers through the MOOC Rumah Vokasi interactive application at one of private vocational school at Surakarta. This service is carried out with a formative evaluation method, through 3 stages: 1. Introduction and training, 2. Apk-based learning implementation, and 3. Evaluation. Based on the evaluation analysis process conducted, it was found that interactive applications play a positive role in helping teachers support learning in the classroom. Relevant features and ease of access are the main keys for teachers to learn new applications that are suitable for use as learning support media. MOOC Rumah Vokasi, able to support teacher candidates and teachers to improve their teaching performance.